2020
DOI: 10.1016/j.bbr.2019.112213
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine replacement improves motor learning of an upper extremity task in people with Parkinson disease

Abstract: Background-Dopamine replacement medication has positive effects on existing motor skills for people with Parkinson disease (PD), but may have detrimental effects on the learning of motor skills necessary for effective rehabilitation according to the dopamine overdose hypothesis.Objectives-This study aimed to determine whether dopamine replacement medication (i.e. levodopa) affects: learning of a novel upper extremity task, decrements in skill following withdrawal of practice, the rate of learning, and the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 45 publications
2
28
0
Order By: Relevance
“…Our laboratory has developed a quick, easy‐to‐administer motor task that objectively evaluates upper extremity dexterity and coordination. This task has been validated against other established upper extremity tasks 28 and is feasible for a wide range of ages and health conditions 29–32 . To summarize, participants are required to use a standard plastic spoon with their non‐dominant hand to acquire two raw kidney beans at a time from a central cup to one of three distal cups arranged at a radius of 16 cm at −40°, 0° and 40° relative to the central cup, starting with the cup ipsilateral to their non‐dominant hand, then to the middle cup, then the contralateral cup.…”
Section: Methodsmentioning
confidence: 99%
“…Our laboratory has developed a quick, easy‐to‐administer motor task that objectively evaluates upper extremity dexterity and coordination. This task has been validated against other established upper extremity tasks 28 and is feasible for a wide range of ages and health conditions 29–32 . To summarize, participants are required to use a standard plastic spoon with their non‐dominant hand to acquire two raw kidney beans at a time from a central cup to one of three distal cups arranged at a radius of 16 cm at −40°, 0° and 40° relative to the central cup, starting with the cup ipsilateral to their non‐dominant hand, then to the middle cup, then the contralateral cup.…”
Section: Methodsmentioning
confidence: 99%
“…For example, injection of DA into the nucleus accumbens restored normal motor activity in rats with reduced motor activity from the injection of 6-hhyroxydopamine causing an 83% DA depletion (15). The loss of dopaminergic neurons and subsequent depletion of DA in the substantia nigra are known to cause the motor deficits observed in Parkinson's disease in both humans and rodent models (16)(17)(18). Dopamine D1 and D2 receptors in the hippocampus and amygdala are associated with anxiety-related behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Although the clinical strategies of alleviating DA-related symptoms in PD by DAergic replacement have been proved highly successful in treating the motor symptoms (233), the effects on motor learning ability remained controversial probably due to different motor tasks being used. One clinical trial on the effect of L-dopa on patients with mild-moderate PD showed improved learning of upper extremity task (234). Another two clinical trials suggested that the L-dopa medication did not significantly alter learning performance of the stepping task in PD patients (235,236).…”
Section: Daergic Enhancementmentioning
confidence: 99%